Self-esteem, emotional intelligence, alcohol consumption, tobacco, social support and academic performance in nursing students - Pérez Briones, Nancy Griselda; Muñoz Morales, Alejandra; Covarrubias Solís, Irma Fabiola; Villa Rivas, Fani; Castillo Díaz, Rocio (Horizonte Sanitario, 2025)
Objetive: Identify the relationship that exists between self-esteem, emotional intelligence, alcohol consumption, tobacco, social support and academic performance in nursing students.Material and methods: Descriptive, cross-sectional and correlational study. The sample was 694 undergraduate nursing students from northern and central Mexico. The instruments used were sociodemographic Data Card, Rosenberg Self-Esteem Sale, Trait Meta Mood Scale-24, CAGE Instrument, Fagestrom Test, Family and Friends Social Support Scale.Results: 80.4% were women, 56.9% reported high self-esteem; 49.3% reported high emotional intelligence, 48.6% consumed alcohol and 17.7% tobacco; 54.6% always have social support. Self-esteem is positively and significantly related to emotional intelligence ((rs= .223, p